Preferential Adsorption of Ethylene Oxide on Fe and Chlorine on Ni Enabled Scalable Electrosynthesis of Ethylene Chlorohydrin. Issue 13 (16th February 2023) - Han, Shuyan; Cheng, Chuanqi; He, Meng; Li, Rui; Gao, Ying; Yu, Yifu; Zhang, Bin; Liu, Cuibo
Abstract: Industrial manufacturing of ethylene chlorohydrin (ECH) critically requires excess corrosive hydrochloric acid or hypochlorous acid with dealing with massive by‐products and wastes. Here we report a green and efficient electrosynthesis of ECH from ethylene oxide (EO) with NaCl over a NiFe2 O4 nanosheet anode. Theoretical results suggest that EO and Cl preferentially adsorb on Fe and Ni sites, respectively, collaboratively promoting the ECH synthesis. A Cl radical‐mediated ring‐opening process is proposed and confirmed, and the key Cl and carbon radical species are identified by high‐resolution mass spectrometry. This strategy can enable scalable electrosynthesis of 185.1 mmol of ECH in 1 h with 92.5 % yield at a 55 mA cm −2 current density. Furthermore, a series of other chloro‐ and bromoethanols with good to high yields and paired synthesis of ECH and 4‐amino‐3, 6‐dichloropyridine‐2‐carboxylicacid via respectively loading and unloading Cl are achieved, showing the promising potential of this strategy. Abstract : Preferential adsorption of ethylene oxide on Fe and chlorine on Ni enabled the electrosynthesis of ethylene chlorohydrin (ECH) with high conversion and selectivity. Scalable production of 185.1 mmol of ECH with 92.5 % yield at 55 mA cm −2 in 1 h, paired synthesis of ECH and 4‐amino‐3, 6‐dichloropyridine‐2‐carboxylic acid (an herbicide), and successful fabrication of a series of other chloro‐ and bromoethanols highlight the potential utilities.